The Names of the Kings of Northern Mesopotamia in Cuneiform Texts : (Subarto, Khamazi, Simorrum) as examples - Hamasharaef, Jaza Sh.; qaradakhi, Asst.Prof. Dr. Rafeda A. Abdulsamad (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract The kings of Northern Mesopotamia had many title which is in fact a reflection of their authority from a political, Social religious and Military aspect and from their titles we can understand the nature of their ruling weather it was religious or military or social. In this research we try to tell about the royal titles which the kings of northern Mesopotamia held, named themselves with and distinguish them in the cuneiform sources because telling about the king is confessing by his authority, telling about the king is confessing by his authority, regarding him as a secured and it is a confess by the width of his authority. The oldest title mentioned in cuneiform sources was EN Which is a religious title in origin, then ENSI which means the prince who was the governor of the city who held civil authority, then LUGAL which meant the king whose authority was bigger than ENSI and he held both religious and civil authority. The LUGAL was king of Sumer and Akkad also the king of four quarter of the world, sometimes the rulers were of military title like (šagina) which means the military leader. This research depend on many cuneiform sources and Archaeological evidences like the cuneiform sources which exist on rocky facades or cylinders seals or other Archeological evidences found during the excavations, which left by the kings of Mesopotamia.